Genome-wide characterization of TCP family and their potential roles in abiotic stress resistance of oat (Avena sativa L.) - Pan, Jing; Ju, Zeliang; Ma, Xiang; Duan, Lianxue; Jia, Zhifeng (Frontiers in Plant Science, 2024)
The TCP gene family members play multiple functions in plant growth and development and were named after the first three family members found in this family, TB1 (TEOSINTE BRANCHED 1), CYCLOIDEA (CYC), and Proliferating Cell Factor 1/2 (PCF1/2). Nitrogen (N) is a crucial element for forage yield; however, over-application of N fertilizer can increase agricultural production costs and environmental stress. Therefore, the discovery of low N tolerance genes is essential for the genetic improvement of superior oat germplasm and ecological protection. Oat (Avena sativa L.), is one of the world’s staple grass forages, but no genome-wide analysis of TCP genes and their roles in low-nitrogen stress has been performed. This study identified the oat TCP gene family members using bioinformatics techniques. It analyzed their phylogeny, gene structure analysis, and expression patterns. The results showed that the AsTCP gene family includes 49 members, and most of the AsTCP-encoded proteins are neutral or acidic proteins; the phylogenetic tree classified the AsTCP gene family members into three subfamilies, and each subfamily has different conserved structural domains and functions. In addition, multiple cis-acting elements were detected in the promoter of the AsTCP genes, which were associated with abiotic stress, light response, and hormone response. The 49 AsTCP genes identified from oat were unevenly distributed on 18 oat chromosomes. The results of real-time quantitative polymerase chain reaction (qRT-PCR) showed that the AsTCP genes had different expression levels in various tissues under low nitrogen stress, which indicated that these genes (such as AsTCP01, AsTCP03, AsTCP22, and AsTCP38) played multiple roles in the growth and development of oat. In conclusion, this study analyzed the AsTCP gene family and their potential functions in low nitrogen stress at the genome-wide level, which lays a foundation for further analysis of the functions of AsTCP genes in oat and provides a theoretical basis for the exploration of excellent stress tolerance genes in oat. This study provides an essential basis for future in-depth studies of the TCP gene family in other oat genera and reveals new research ideas to improve gene utilization.